2020
DOI: 10.48550/arxiv.2004.02729
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drawing together control landscape and tomography principles

Christian Arenz,
Herschel Rabitz

Abstract: The ability to control quantum systems using shaped fields as well as to infer the states of such controlled systems from measurement data are key tasks in the design and operation of quantum devices. Here we associate the success of performing both tasks to the structure of the underlying control landscape. We relate the ability to control and reconstruct the full state of the system to the absence of singular controls, and show that for sufficiently long evolution times singular controls rarely occur. Based … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Extensive QOC simulation and laboratory studies indicate the relative ease of satisfying all three assumptions [44]. Furthermore, it has been shown that assumptions (1) and ( 3) are almost always satisfied in a measure theoretic sense [68,110,111], thereby implying that QOC landscapes are almost always free of local minima under the premise of sufficient control field resources [112]. While the precise meaning of "sufficient" is application-dependent and remains an open challenge to systematically assess, it has recently been shown that local surjectivity is almost always met when the control fields allow for approximating Haar random evolutions [111,113] within the time interval of interest: [0, T ].…”
Section: B Optimization Landscapesmentioning
confidence: 96%
See 2 more Smart Citations
“…Extensive QOC simulation and laboratory studies indicate the relative ease of satisfying all three assumptions [44]. Furthermore, it has been shown that assumptions (1) and ( 3) are almost always satisfied in a measure theoretic sense [68,110,111], thereby implying that QOC landscapes are almost always free of local minima under the premise of sufficient control field resources [112]. While the precise meaning of "sufficient" is application-dependent and remains an open challenge to systematically assess, it has recently been shown that local surjectivity is almost always met when the control fields allow for approximating Haar random evolutions [111,113] within the time interval of interest: [0, T ].…”
Section: B Optimization Landscapesmentioning
confidence: 96%
“…Furthermore, it has been shown that assumptions (1) and ( 3) are almost always satisfied in a measure theoretic sense [68,110,111], thereby implying that QOC landscapes are almost always free of local minima under the premise of sufficient control field resources [112]. While the precise meaning of "sufficient" is application-dependent and remains an open challenge to systematically assess, it has recently been shown that local surjectivity is almost always met when the control fields allow for approximating Haar random evolutions [111,113] within the time interval of interest: [0, T ]. As such, even though performing the optimization over a set of parametrized control fields does not avoid the non-convexity of the problem, provided the assumptions (1)-(3) hold, the interior of the optimization landscape provably contains saddles only.…”
Section: B Optimization Landscapesmentioning
confidence: 99%
See 1 more Smart Citation